2014
DOI: 10.1007/s13224-014-0537-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study to Evaluate the Intersystem Association and Reliability Between Standard Pelvic Organ Prolapse Quantification System and Simplified Pelvic Organ Prolapse Scoring System

Abstract: There is almost perfect intersystem agreement between the S-POP classification system and the standard POPQ classification system in respect of the overall stage as well as each point within the same system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Studies by Manonai et al and Raizada et al showed better results (0.71 and 0.86 respectively). 11,13 There was excellent agreement for cervix (0.9) and posterior fornix (0.87) which is in congruent to the studies. 11,13 There was good agreement between the two classification systems of POP.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Studies by Manonai et al and Raizada et al showed better results (0.71 and 0.86 respectively). 11,13 There was excellent agreement for cervix (0.9) and posterior fornix (0.87) which is in congruent to the studies. 11,13 There was good agreement between the two classification systems of POP.…”
supporting
confidence: 83%
“…This has made its widespread acceptance and use limited by the practicing clinicians. [8][9][10][11] In response to this, International Urogynecological Association (IUGA) Standardization of Terminology Committee has devised a simplified version of POPQ (S-POP) classification system that retains the ordinal stages of POP-Q system but simplifies terminology and reduces number of points measured, for easy translation into daily clinical practice. 12,13 Hence with this aim the present study was planned to determine the agreement between standard POPQ system and simplified POP scoring system and to propose a userfriendly scoring system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only problem with the POP-Q technique is its complexity for the beginners to understand and the time consumed for the total examination. A six-point simplified version of POP-Q was suggested by Raizada N et al as SPOP-Q [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This system has shown good reliability, taking 9 points into consideration. However, the conventional system is found to be timeconsuming, difficult to learn and implement in daily practice, hence, a 6 point simplified version of POP-Q has been tried by Raizada Nivedita et al [9] which has given good correlation between POP-Q and SPOP-Q.…”
mentioning
confidence: 99%